Effects of gas absorption with chemical dissociation reaction on single slurry droplet drying. Issue 5 (3rd April 2020) - Pour, Yehonatan David; Fominykh, Andrew; Krasovitov, Boris; Levy, Avi
Abstract: A theoretical model of the absorption of soluble gases during the first stage of slurry droplet drying, at or below room temperature and at atmospheric pressure, is suggested as a basis for the development of alternative drying methods. The suggested approach is based on the theory of slurry droplet evaporation, in conjunction with a model of chemical absorption by evaporating droplets. Slurry droplet evaporation is described by a system of transient conjugate nonlinear energy and mass conservation equations. Numerical calculations are performed for a slurry droplet evaporating in various gaseous mixtures, including a gaseous mixture containing soluble gases. It is shown that the effect of gas absorption is a significant enhancement in the rate of evaporation of a slurry droplet, with higher concentrations of soluble gas in the gas phase leading to a shorter first stage of drying. In particular, in a ternary gaseous mixture (N2 /NH3 /H2 O) with an ammonia mass fraction of 0.5 and at 288 K, the evaporation time of a coal-water slurry droplet with an initial radius of 100   µ m was about 20% shorter than that in a mixture free of soluble gases. The existence of a maximum in the temporal dependence of the interfacial temperature of the droplet during evaporation is also revealed. This maximum becomes more pronounced with increasing ambient concentration of the absorbate. Calculations show that relative humidity exerts a minor influence on the dynamics of gas absorption by liquid droplets. By contrast, relative humidity strongly affects the rate of evaporation of slurry droplets. The model for slurry droplet evaporation in the presence of soluble gas presented herein allows for calculation of the appropriate concentration of soluble gas in the gaseous phase to achieve an optimal regime for slurry droplet drying.